Interaction between the α-T catenin gene (VR22) and APOE in Alzheimer's disease. Issue 10 (30th September 2005) - Martin, E R; Bronson, P G; Li, Y-J; Wall, N; Chung, R-H; Schmechel, D E; Small, G; Xu, P-T; Bartlett, J; Schnetz-Boutaud, N; Haines, J L; Gilbert, J R; et al.
Abstract : Background: APOE is the only gene that has been consistently replicated as a risk factor for late onset Alzheimer's disease. Several recent studies have identified linkage to chromosome 10 for both risk and age of onset, suggesting that this region harbours genes that influence the development of the disease. A recent study reported association between single nucleotide polymorphisms (SNPs) in the VR22 gene (CTNNA3) on chromosome 10 and plasma levels of Aβ42, an endophenotype related to Alzheimer's disease. Objective: To assess whether polymorphisms in the VR22 gene are associated with Alzheimer's disease in a large sample of Alzheimer's disease families and an independent set of unrelated cases and controls. Results: Several SNPs showed association in either the family based or case–control analyses (p<0.05). The most consistent findings were with SNP6, for which there was significant evidence of association in both the families and the unrelated cases and controls. Furthermore, there was evidence of significant interaction between APOE-4 and two of the VR22 SNPs, with the strongest evidence of association being concentrated in individuals carrying APOE-4. Conclusions: This study suggests that VR22 or a nearby gene influences susceptibility to Alzheimer's disease, and the effect is dependent on APOE status.